KEHIDUPAN SOSIAL BUDAYA PASANGAN SUAMI ISTRI PASCA ADAT PASU-PASU RAJA PADA ETNIS BATAK TOBA DI KECAMATAN TARUTUNG TAPANULI UTARA - Nainggolan, Agustina; Nasution, Rosramadhana (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This research aims to describe the socio-cultural life of Toba Batak husband and wife couples after marriage according to the pasu-pasu raja custom. The type of research used is qualitative research with an ethnographic approach. The data collection technique used in this research is through participant observation with the aim that the author can understand in depth the socio-cultural life of married couples who are adapting to the post-pasu-pasu raja custom based on what the author sees, feels and hears. Apart from that, we also conducted in-depth interviews and documentation. The results of this research reveal conditions where it is not permissible to visit the wife's family before carrying out the Toba Batak traditional wedding stage, namely manuruk-nuruk. Feelings of shame arise towards parents because they have disappointed them. Then husband and wife are not allowed to receive and give ulos at any traditional event as long as they have not held an official traditional event. If one day their children want to get married but their parents have not yet done their best, then they will not be able to marry their children. Furthermore, the efforts made by husband and wife to be able to face all the consequences they receive after getting married after the pasu-pasu raja custom is to work diligently to collect sinamot or dowry money so that they can hold traditional parties, whether small traditional parties or large traditional parties. Based on the research results above, it can be concluded that with the efforts made by husband and wife couples in dealing with the socio-cultural life they are going through, there are adaptations that must be faced in responding to post-marriage socio-cultural life according to the traditional pasu-pasu raja of the Toba Batak ethnic group in Tarutung District.